Hazardous alcohol use and HIV indicators in six African countries: results from the Population‐based HIV Impact Assessments, 2015–2017. Issue 11 (21st November 2022) - Chang, Gregory C.; West, Christine A.; Kim, Evelyn; Low, Andrew J.; Lancaster, Kathryn E.; Behel, Stephanie S.; Hong, Steven Y.; Miller, Leigh Ann; Silver, Rachel; Mgomella, George S.; Imaa, Jennifer; Maokola, Werner M.; et al.
Abstract: Introduction: Hazardous alcohol use (HAU), defined as a pattern of alcohol consumption that increases the risk of harmful consequences for the user or others, is associated with an elevated risk of human immunodeficiency virus (HIV) infection and poor health outcomes. We describe the association between people living with HIV (PLHIV) who report HAU and key HIV indicators. Gaps in current literature in estimating HAU on HIV outcomes at the regional level of Eastern and Southern Africa still exist and our analysis aims to address this issue. Methods: We used weighted pooled data (2015–2017) from the nationally representative Population‐based HIV Impact Assessments among adults who provided written consent aged 18–59 years from Eswatini, Malawi, Namibia, Tanzania, Zambia and Zimbabwe. We estimated differences in the prevalence of HIV infection and The Joint United Nations Programme on HIV and AIDS (UNAIDS) 90‐90‐90 indicators between PLHIV by HAU status using log‐binomial regression, stratified by sex. HAU was determined using the Alcohol Use Identification Test—Consumption. Results: Among the 9755 women and 4444 men who tested HIV positive, 6.6% of women and 21.8% of men engaged in HAU. Women who reported HAU were more likely to be HIV positive (adjusted prevalence ratio [aPR] = 1.31, 95% CI: 1.18–1.46) compared to those who did not report HAU. For the UNAIDS 90‐90‐90 targets, women who engaged in HAU were more likely to be unaware of their HIV‐positive status (aPR = 1.22, 95% CI: 1.01–1.47) and not on antiretroviral therapy (ART) (aPR = 1.73, 95% CI: 1.26–2.37). Men who engaged in HAU were more likely to be unaware of their HIV‐positive status (aPR = 1.56, 95% CI 1.39–1.76) and not on ART (aPR = 1.72, 95% CI: 1.30–2.29). No difference in viral load suppression, defined as <1000 copies/ml of HIV RNA, was seen by sex. Conclusions: PLHIV who engage in HAU were more likely to have suboptimal outcomes along the HIV care continuum when compared to those who did not engage in HAU. Targeted interventions, such as alcohol screening for HAU in HIV testing and treatment settings and HIV prevention efforts in alcohol‐based venues, may help countries reach HIV epidemic control by 2030.